2024
DOI: 10.1002/smsc.202300350
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman Microscopy to Image Microstructure Changes in Silicon Phthalocyanine Thin‐Films

Rosemary R. Cranston,
Taylor D. Lanosky,
Raluchukwu Ewenike
et al.

Abstract: The choice of deposition technique and post deposition treatment can significantly influence the performance of organic electronic devices by altering the complex relationship between film properties and charge transport. Herein, the influence of deposition method and post deposition thermal annealing on the thin‐film properties of an emerging semiconductor, bis(tri‐n‐propylsilyl oxide) SiPc ((3PS)2‐SiPc), is examined by polarized Raman microscopy. Comparing physical vapor deposition (PVD) and spin‐coating, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…To further examine the thin films, we employed polarized Raman microscopy. We, and others, have demonstrated that quantifying the intensity changes in Raman signals associated with the in-plane bonds of small-molecule semiconductors with different laser polarities makes it possible to extract the molecular orientation relative to the surface (Figure c). When applying this analysis across each pixel, we can provide average molecular orientation maps that demonstrate the degree of edge-on versus face-on orientation across the film.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the thin films, we employed polarized Raman microscopy. We, and others, have demonstrated that quantifying the intensity changes in Raman signals associated with the in-plane bonds of small-molecule semiconductors with different laser polarities makes it possible to extract the molecular orientation relative to the surface (Figure c). When applying this analysis across each pixel, we can provide average molecular orientation maps that demonstrate the degree of edge-on versus face-on orientation across the film.…”
Section: Resultsmentioning
confidence: 99%
“…Cl-AlPc has a reactive chloro axial group, which can be easily modified through phenoxylation reactions, leading to a handle for engineering the solid-state interactions in the thin film. Our group has employed this strategy to improve silicon phthalocyanine (R 2 -SiPc)-based OTFTs , and ammonia sensors , with great success. Therefore, we synthesized a series of phenoxylated Cl-AlPcs (phenoxy-AlPc) and compared them with the baseline Cl-AlPc .…”
Section: Optimization Of Otft Cannabinoid Sensorsmentioning
confidence: 99%